The Cells of Innate Systems in Tick-Borne Encephalitis - Plekhova, Natalia G.; Somova, Larisa M.; Lyapun, Irina N.; Kondrashova, Nadejda M.; Krylova, Natalia V.; Leonova, Galina N.; Pustovalov, Euvgenii V. (IntechOpen, 2011)
None